Legal Drinking, Injury and Harm: Evidence from the Introduction and Modifications of Age Limits in Denmark - Nabanita Datta Gupta; Anton Nilsson (Institute of Labor Economics (IZA), 2020)
Alcohol is considered one of the most serious threats to population health, and to mitigate its negative consequences, most countries have implemented policies such as minimum legal drinking ages (MLDAs). Denmark, a country with an exceptionally liberal youth alcohol culture, introduced a minimum age for purchasing alcoholic beverages as late as in 1998, prohibiting those below 15 to buy alcohol. Previous studies from the U.S. and a few other contexts have provided substantial evidence that MLDA legislations influence outcomes such as car accidents, but there is little evidence from Europe. Moreover, there is limited evidence for injuries other than those due to vehicle accidents. We exploit the introduction and changes in the MLDA in Denmark to estimate effects on all classes of injuries, as well as alcohol-related outcomes such as intoxication and poisoning. We bring comprehensive evidence on the effects of a total of three reforms, which affected alcohol availability along different margins – 1) establishing an off-premise alcohol purchase age of 15 (1998), 2) raising the off-premise alcohol purchase age to 16 (2004), and 3) increasing the purchase age of beverages exceeding 16.5% in alcohol content from 16 to 18 (2011). Our findings show significant impacts of all the three reforms on injuries. We find that girls responded more to two first two reforms influencing alcohol availability, whereas boys responded more to the last reform, influencing availability of strong liquor. On the other hand, no consistent differences were found across different socioeconomic groups, perhaps reflecting similar patterns of drinking.
Keywords: H00; I00; I12; 330; alcohol; minimum legal drinking ages; Difference-in-Differences; Denmark